A pele dos anfíbios como fontes de biomarcadores para estudos de monitoramento ambiental: uma revisão bibliográfica sistemática - Chiaperini, Matheus Henrique da Silva (2026)
Amphibians constitute a broad and diverse group and are considered reliable bioindicator models due to their high sensitivity to environmental changes. Amphibian skin is a semipermeable, vascularized organ endowed with multiple functions and complex characteristics, which can be used as valuable tools in ecotoxicological studies. However, the application of cutaneous biomarkers in amphibian research remains limited and scattered throughout the literature, which may hinder an integrated understanding of their potential as well as their possible limitations. Therefore, the aim of this study was to conduct a systematic literature review, critically analyzing scientific publications on cutaneous biomarkers that have been employed in ecotoxicological studies involving amphibians. To this end, a qualitative–quantitative systematic literature search was carried out, focusing on articles published between 1900 and 2024. Searches were performed using web-based search tools and scientific databases (Google Scholar, Scopus, Web of Science, PubMed, and ScienceDirect), applying specific combinations of keywords and selecting and classifying articles according to predefined eligibility criteria. The screening process resulted in 54 articles published worldwide, demonstrating that these specific types of biomarkers remain underestimated in scientific research. The geographical distribution of the studies revealed a predominance of publications from European and Latin American countries. Among the experimental models, adult-stage anurans were the most frequently used, and the sex of the individuals was not reported in most studies (74.1%). The results also showed a predominance of studies that did not report the anatomical region of the skin used as the source of cutaneous tissue samples (e.g., ventral, dorsal, lateral skin). Regarding ecotoxicological assay types, studies involving direct dermal exposure and acute exposure durations predominated, indicating a greater interest in simulating immediate effects in toxicological assays. The most frequently studied contaminant classes were agrochemicals and metals, reflecting a preference for more “classical” toxicants in toxicology, while emerging contaminants remained underrepresented, such as industrial residues (3.2%) and radiation (6.4%). The most commonly applied biomarker classes were physiological analyses (33.9%), followed by histological (32.2%) and morphological (18.6%) assessments, highlighting the relevance of the skin as one of the main routes of entry and absorption for various environmental compounds. Overall, our findings not only compiled and organized relevant ecotoxicological data for amphibian studies but also highlighted several methodological limitations that still need to be addressed in future research. It is expected that this compilation may serve as a robust and relevant foundation to encourage further studies to expand the application of cutaneous biomarkers as a promising tool in amphibian research.